Stabilisation of switched linear systems under denial of service - Qu, Hanqing; Zhao, Jun (IET control theory & applications, 2020)
The authors consider the stabilising problem for switched linear systems subject to denial-of-service (DoS) attacks that block communications on the network. Using the periodic sampled-data control, the authors first research the switched systems where no DoS attacks occur, and a class of switching signals satisfying the average dwell time is presented to stabilise the switched systems in which the authors take asynchronous switching into consideration. Then, using the presented switching signals, a sufficient condition with respect to DoS attack duration and frequency is given to keep switched systems stable under DoS attacks. The condition reflects the relation between attack rate and system stability. The authors also analyse the qualitative relation between average dwell time and system robustness against attacks. Compared with non-switched systems, the analysis of switched systems under DoS attacks is more challenging. They finally give a numerical example to show the validity of the result.